Regionalism, multilateralism, and economic integration : the recent experience - Sampson, Gary P.; Woolcock, Stephen (United Nations University Press, 2003)
Have regional trade agreements led to a new form of economic cooperation by promoting deeper integration in the regulatory structures of participating countries? The answer has profound i m p l ications for the future of multilateral cooperation and international economic relations. Regional trade agreements have led to deeper integration in a number of fields, and recent agreements are generally more effective than the more remote WTO procedures in facilitating t rade and improving transparency. There is no single model for deeper i n t e g ration and each t rade agreement is the result of attempts to achieve very different policy objectives. But Regionalism, Multilateralism, and Economic Integration finds that regional processes and rules have been consistent with the multilateral obligations of each party. WTO rules therefore constitute a floor that underpins additional commitments in the regional agreements.